A case of academic social networking sites usage in Malaysia: drivers, benefits, and barriers - Salahshour, M. (IGI Global, 2016)
Social networking tools have become an integral part of our daily lives. Recently, a new type of Social Networking Sites (SNSs) namely Academic Social Networking sites (ASNSs) has attracted global users. There is perceived usefulness on the impact of ASNSs on patterns of academic research activities. However, it remains unclear why some researchers do not use ASNSs at all. The purpose of this paper is therefore to explore the ASNSs usage among Malaysian academic researchers and to investigate benefits, specific purpose, drivers and barriers of using ASNSs. A total of 210 completed cases were collected through paper-based and online-based questionnaire. In order to show the outcome of the research, descriptive interpretation of data is performed. The overall findings of this research indicate that there is low rate of ASNSs usage among researchers. In addition, the results show that colleagues, attitude toward technology and communication benefits are the drivers to use ASNSs and trust, privacy and security are the common barriers regarding to use ASNSs.